Over a million students use our free study notes to help them with their homework
fg(x) means f of g of x
fg(x) = 3(cx+8) + c = 3cx + 24 + c = 6x + d
3cx = 6x 3c=6 c=2
24 + c = d 24+2=d=26
The quadratic formula is used to solve the quadratic equation. Although methods like factorising or completing the square can easily be used, this offers another method which can be used for more difficul...
Parallel lines have the same gradient (same 'm' value in y=mx+c). Therefore m=3 for both equations; if they are parallel lines. The second equation needs to be rearranged for y to determine this. 3y-9x+5 ...
7(x + 2)
7x+y=1 (1) -> y= 2x2 - 3 (3)
7x + 2x2 -3-1=0 -> (2x-1)(x+4)=0 so 2x-1=0 so 2x=1 so x=0.5 and x+4=0 so x=-4
7(0.5)+y=1 so y=1-3.5 so y=-2.5 and 7(-4) +y=1 so -2...
←
663
664
665
666
667
→
Internet Safety
Payment Security
Cyber
Essentials